Changes of traffic network and urban transformation: A case study of Xi'an city, China. (November 2019) - Zeng, Zhaozhao; Song, Bingjie; Zheng, Xiaodong; Li, Huan
Highlights: road network density, road network connectivity and traffic service capability are improved by 72.7%, 58.3% and 33.3% respectively after UT. Urban traffic system plays a decisive role in structuring urban morphology. Perfect traffic network can not only promote urban space optimization. Abstract: Urban traffic system plays a decisive role in structuring urban morphology. Sustainable traffic network can not only promote urban structure optimization, but also can achieve sustainable urban transformation (UT). Xi'an, one of the most important central cities in Western China, is selected as the research area. This research analyzes the change of traffic network in the process of UT by using road network density, road network connectivity and traffic service capability indexes to quantify the development of traffic during different period. The results shows that these three indexes are improved by 72.7%, 58.3% and 33.3% respectively after starting UT. (1) After starting UT, the expansion speed of high road network density area was far than speed before. The medium density area spread to the surrounding counties to form the network. (2) High road connectivity areas expanded rapidly and extended to the north and south, while the areas with low value area had not been effectively developed. (3) High traffic service capability area gradually aggregated, mainly extended to south and central of Xi'an We conclude that urban transformation has a positive effect on changes of urban traffic network, and urban traffic network also can promote sustainable urban transformation.